Design and manufacture of bioresorbable cavitation agents - Swathy, Elavarasan (2018)
Atherosclerosis is a chronic inflammatory cardiovascular disease characterized by the formation of plaques by the build-up of lipids in the arterial wall. These atherosclerotic plaques evoke an immune response and become unstable, shedding the lipid deposits and other indurated matter into the lumen. These atherosclerotic lesions subsequently become nuclei for thrombi occluding the blood flow leading to myocardial infarction, pulmonary thromboembolism or ischemic stroke. The treatment of atherosclerosis is limited by the inability to deliver effectively and safely the therapeutics across the endothelium. The atherosclerotic lesions represent a biological barrier that impedes the delivery of drugs by passive diffusion. Developing an effective targeting and delivery method would lead to a paradigm shift in the development of more reliable, more economical and less-invasive treatments. Targeted therapy for atherosclerosis is achievable using ultrasound-induced bubble oscillations to transport and implant drug-loaded bioresorbable cavitation agents at the site of lesion. By combining both extracorporeal or intravascular ultrasound and novel cavitationinducing drug –loaded bioresorbable particles an effective targeted drug delivery system can be developed. In this report, the focus is on designing a novel cavitation agent and test if it is responding to ultrasound by exhibiting stable cavitation.